Double‐blind, randomized clinical trial assessing the efficacy and safety of early initiation of sitagliptin during metformin uptitration in the treatment of patients with type 2 diabetes: The CompoSIT‐M study. Issue 5 (17th February 2019) - Frias, Juan P.; Zimmer, Zachary; Lam, Raymond L.H.; Amorin, Guillermo; Ntabadde, Catherine; Iredale, Carol; O'Neill, Edward A.; Engel, Samuel S.; Kaufman, Keith D.; Makimura, Hideo; Crutchlow, Michael F.
Abstract : Aims: To characterize the glycaemic efficacy and safety of initiation of the dipeptidyl peptidase‐4 inhibitor sitagliptin during metformin dose escalation in people with type 2 diabetes (T2D) not at glycated haemoglobin (HbA1c) goal on a sub‐maximal dose of metformin. Materials and methods: Study participants with HbA1c ≥58 mmol/mol and ≤97 mmol/mol (≥7.5% and ≤11.0%) while on 1000 mg/d metformin were randomized to sitagliptin 100 mg once daily or placebo. All were to uptitrate metformin to 2000 mg/d. A longitudinal data analysis model was used to test the primary hypothesis that sitagliptin is superior to placebo when initiated during uptitration of metformin in reducing HbA1c at week 20. [ClinicalTrials.gov Identifier: NCT02791490, EudraCT: 2015‐004224‐59] Results: A total of 458 participants (mean HbA1c 71.1 mmol/mol [8.7%], T2D duration 6.3 years) were treated. After 20 weeks, the least squares (LS) mean changes from baseline in HbA1c were −12.1 mmol/mol (−14.0, −10.1) (−1.10% [−1.28, −0.93]) and −7.6 mmol/mol (−9.6, −5.6) (−0.69% [−0.88, −0.51]) with sitagliptin and placebo, respectively; the between‐group difference in LS mean changes from baseline HbA1c was −4.5 mmol/mol (−6.5, −2.5) (−0.41% [−0.59, −0.23]); P < 0.001. The likelihood of having HbA1c <53 mmol/mol (<7.0%) at week 20 was higher in the sitagliptin group than in the placebo group in the overall population (relative risk 1.7, P = 0.002) and in those with a baseline HbA1c ≥69 mmol/mol (≥8.5%) (relative risk 2.4, P = 0.026). There were no notable differences between groups with regard to adverse events overall, hypoglycaemia events, changes in body weight or other safety variables. Conclusion: In participants not at HbA1c goal on a sub‐maximal dose of metformin, addition of sitagliptin at the time of metformin dose uptitration improved glycaemic response and HbA1c goal attainment, with similar safety and tolerability, compared to metformin uptitration alone.